Unna Boot Therapy Reduces Emergency Department Use in an Unhoused Patient: A Case Report - Ariana Coba Clementel; Frank Ross (Clinical Practice and Cases in Emergency Medicine, 2026)
Introduction: Venous leg ulcers disproportionately affect people experiencing homelessness and contribute to recurrent emergency department (ED) use. Standard wound care protocols often require daily dressing changes and leg elevation, which are unrealistic in unstable housing environments. Case Report: A 71-year-old male with a 10-year history of venous leg ulcers and 15 ED visits achieved complete wound epithelialization after four months of weekly Unna boot compression therapy, despite eviction during treatment. He has not returned to the ED for this condition. Conclusion: Emergency department-initiated compression therapy with structured wound care referral may reduce recurrent ED use among unhoused patients with venous leg ulcers.